Exploring the Effectiveness of Blended Learning Models in Higher Education: A Case Study of Indonesian Universities - Nisak, Sayida Khoiratun; Latifah, Nur; Martin; Ummah, S. Sumihatul; Yusup, Muhammad (Academy of Education Journal, 2025)
The research aimed to test the blended learning model in Indonesian higher education. To this end, a qualitative approach was adopted, employing a case study method to collect data. This method included in-depth interviews, observations, and a thorough document analysis. This research found that blended learning improves flexibility, engagement, and effectiveness. However, this improvement depends on two key elements. First, a good tech infrastructure. Second, lecturers skilled in using tech tools. We must, however, recognize obstacles that limit this approach's full potential. Impediments include, but are not limited to, disparities in internet access and a lack of training for lecturers to use technology. This study's insights can guide effective blended learning in higher education.